THE SPEAKING ASSESSMENT OF SMPS MELATI BINJAI - Rosmen; Supriadi; Irhamni (The Seall Journal, 2020)
This study analysed the implementation of a speaking assessment administered by the teacher in the speaking class. The study was held at the grade VII of SMPS Melati Binjai. The data were collected through classroom observation, document analysis and interview validation. The data showed that the assessment administered by the teacher was provided as required by the K13. It was confirmed that the appropriateness of the speaking assessment addressed in thespeaking class by the teacher was suitable. It was considered that there should be an effort to initiate a well-understood teacher in providing a sufficient assessment. A periodical MGMP activities held by the Government/Diknas exceptionally encouraging teacher’s understanding in interpreting the K13’s expectations. MGMP was condisedered hugely helped teachers solved any hinders and obstacles in the instructional processes. Thus, further studies of theimplementation of a proposed assessment which is required by the K13 expected brought in order to contriving a better evaluation.